Liver transplant for giant cell hepatitis with autoimmune haemolytic anaemia. Issue 3 (1st September 1997) - Melendez, Hector Vilca; Rela, Mohamed; Baker, Alastair J; Ball, Colin; Portmann, Bernard; Mieli-Vergani, Giorgina; Heaton, Nigel D
Abstract : Giant cell hepatitis (CGH) with autoimmune haemolytic anaemia (AHA) is a distinct entity with an aggressive course. Immunosuppression may help early disease. A case is reported of a child with GCH and AHA with early disease recurrence after liver transplantation for end stage liver disease.